2015
DOI: 10.1038/tp.2015.132
|View full text |Cite
|
Sign up to set email alerts
|

Rewriting the valuation and salience of alcohol-related stimuli via memory reconsolidation

Abstract: The transient period of memory instability that can be triggered when memories are retrieved under certain conditions offers an opportunity to modify the maladaptive memories at the heart of substance use disorders (SUDs). However, very well-learned memories (such as those in excessive drinking and alcohol use disorders) are resistant to destabilisation when retrieved or may not destabilise at all. Memory retrieval and intervention procedures that reliably destabilise and update maladaptive motivational memori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 67 publications
9
119
3
Order By: Relevance
“…Therefore, utilizing the retrieval-counterconditioning procedure to replace these unwanted memories with adaptive memories is a potentially novel behavioral therapeutic approach for these neuropsychiatric disorders. Indeed, Das et al (2015) recently demonstrated that human hazardous drinkers expressed less attention bias towards alcohol-related stimuli after exposure to aversive taste or pictures during reconsolidation, further pointing to the translational value of the present approach to reduce cue-induced craving and relapse in drug addicts.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, utilizing the retrieval-counterconditioning procedure to replace these unwanted memories with adaptive memories is a potentially novel behavioral therapeutic approach for these neuropsychiatric disorders. Indeed, Das et al (2015) recently demonstrated that human hazardous drinkers expressed less attention bias towards alcohol-related stimuli after exposure to aversive taste or pictures during reconsolidation, further pointing to the translational value of the present approach to reduce cue-induced craving and relapse in drug addicts.…”
Section: Discussionmentioning
confidence: 77%
“…Neutral context memory can acquire threatening properties when reconsolidation mediates the incorporation of new threat learning experience [36]; contextual threat memories can strengthen with additional learning after retrieval in a process depending selectively on reconsolidation mechanisms [37]; and appetitive associative memories can lose their rewarding properties using the reactivation-extinction procedure [38, 39]. Another updating process that has effectively reduced reward-related responding involves reactivation followed by counterconditioning [4042], where the appetitive conditioned stimulus is paired with an aversive outcome during reconsolidation.…”
Section: Reconsolidation Updates Memoriesmentioning
confidence: 99%
“…Taking a potentially more robust approach, a recent study used reactivation followed by counterconditioning in hazardous alcoholic drinkers [40]. The study induced memory reactivation using an actual alcoholic drink as the reminder, which the participants were almost allowed to drink but were stopped.…”
Section: Translation Of Memory Reconsolidation Updatingmentioning
confidence: 99%
“…For example, in hazardous alcohol drinkers, post-retrieval ethanol cue reappraisal or counterconditioning blocked reconsolidation in a retrieval-dependent manner (Das et al 2015b; Hon et al 2015). Furthermore, in these studies, no behavioral effect was elicited when the design did not explicitly elicit a prediction error, which is thought to enhance memory lability memory and initiate reconsolidation (Exton-McGuinness et al 2015; Torregrossa and Taylor 2016; Corlett and Taylor 2013).…”
Section: Reconsolidation In Clinical Populationsmentioning
confidence: 99%